The fate of Saul's progeny in the reign on David - Tushima, Cephas T. A. (James Clarke, 2012)
Cephas Tushima provides a thorough analysis of the fate of Saul's heirs, focussing on whether their tragedies were due to continuing divine retribution, coincidence, or Davidic orchestration. He concludes that David was unjust and calculating in his dealings with the Saulides and, like other Near Eastern usurpers, perpetrated heinous injustices against the vanquished house of Saul. Traditionally readers saw Saul as evil and David as a hero; but more recently scholars have written about Saul as a tragic character and David as a villain, turning the book of Samuel into deeply contested interpreti.